Acetylcholine Release Inhibits Distinct Excitatory Inputs Onto Hippocampal CA1 Pyramidal Neurons via Different Cellular and Network Mechanisms - Goswamee, Priyodarshan; McQuiston, A. Rory (Frontiers in Cellular Neuroscience, 2019)
In hippocampal CA1, muscarinic acetylcholine (ACh) receptor (mAChR) activation via exogenous application of cholinergic agonists has been shown to presynaptically inhibit Schaffer collateral (SC) glutamatergic inputs in stratum radiatum (SR), and temporoammonic (TA) and thalamic nucleus reuniens (RE) glutamatergic inputs in stratum lacunosum-moleculare (SLM). However, steady-state uniform mAChR activation may not mimic the effect of ACh release in an intact hippocampal network. To more accurately examine the effect of ACh release on glutamatergic synaptic efficacy, we measured electrically evoked synaptic responses in CA1 pyramidal cells (PCs) following the optogenetic release of ACh in genetically modified mouse brain slices. The ratio of synaptic amplitudes in response to paired-pulse SR stimulation (stimulus 2/stimulus 1) was significantly reduced by the optogenetic release of ACh, consistent with a postsynaptic decrease in synaptic efficacy. The effect of ACh release was blocked by the M3 receptor antagonist 4-DAMP, the GABAB receptor antagonist CGP 52432, inclusion of GDP-β-S, cesium, QX314 in the intracellular patch clamp solution, or extracellular barium. These observations suggest that ACh release decreased SC synaptic transmission through an M3 muscarinic receptor-mediated increase in inhibitory interneuron excitability, which activate GABAB receptors and inwardly rectifying potassium channels on CA1 pyramidal cells. In contrast, the ratio of synaptic amplitudes in response to paired-pulse stimulation in the SLM was increased by ACh release, consistent with presynaptic inhibition. ACh-mediated effects in SLM were blocked by the M2 receptor antagonist AF-DX 116, presumably located on presynaptic terminals. Therefore, our data indicate that ACh release differentially modulates excitatory inputs in SR and SLM of CA1 through different cellular and network mechanisms.